Multispectral estimation of retinal photoreceptoral inputs - Bara, Salvador; Bonmati-Carrion, Maria Angeles; Madrid, Juan Antonio; Rol, Maria Angeles; Zamorano, Jaime (Photonics Letters of Poland, 2019)
Integrated multispectral devices provide convenient means for assessing the inputs to the five known photoreceptors present in the human retina. These photoreceptors drive relevant visual and non-visual pathways that control key aspects of human physiology. In this Letter we show that standard metrics of retinal photoreceptoral exposure can be quantitatively estimated, to within a 5%, by means of 12 multispectral channels, 20 nm wide (FWHM), distributed across the visible range. Full Text: PDF References D.M. Berson, F.A. Dunn, M. Takao, "Phototransduction by Retinal Ganglion Cells That Set the Circadian Clock", Science 295, 1070 (2002). CrossRef R.J. Lucas et al. "Measuring and using light in the melanopsin age", Trends in Neurosciences 37, 1 (2014). CrossRef Commission Internationale de l’Eclairage. TN 003:2015 Report on the First International Workshop on Circadian and Neurophysiological Photometry, 2013. CIE, 2015. DirectLink A. Sánchez de Miguel et al, "Evaluating Human Photoreceptoral Inputs from Night-Time Lights Using RGB Imaging Photometry", Journal of Imaging 5(4), 49 (2019). CrossRef M.S. Rea, M.G. Figueiro, A. Bierman, R. Hamner. "Modelling the spectral sensitivity of the human circadian system", Lighting Research and Technology 44, 386 (2012). CrossRef D. Cao, P.A. Barrionuevo, "Estimating photoreceptor excitations from spectral outputs of a personal light exposure measurement device", Chronobiology International 32(2), 270 (2015). CrossRef P.B. Liebelt, An Introduction to Optimal Estimation (Reading, MA, Addison-Wesley, 1967). CrossRef J. Escofet, S. Bará, "Reducing the circadian input from self-luminous devices using hardware filters and software applications", Lighting Research and Technology 49, 481 (2017). CrossRef